Adoption of the New Romanian Civil Code and Some Effects Thereof on the Business Law - COJOCARU, Cristina (Journal of Advanced Research in Law and Economics; Vol 4 No 2 (2013): JARLE Volume IV Issue 2(8) Winter 2013, 2016)
On 1st October 2011 a new Romanian Civil code has been enacted, which has included therein the regulations of commercial law. This new regulation meant not only taking some provisions from the former Commercial Code, thus repealed, but also redefining some institutions of business law and placing them in another context. Thus, the notion of trader, respectively professional, has been redefined, some contracts of a commercial nature have been introduced or regulated differently, new institutions have been introduced and a unitary regulation has been accomplished, in which the business law has been included in the larger sphere of civil law
Keywords: Romanian Civil Code, business law, trader, commercial contracts, unitary regulation, private law